2017
DOI: 10.1248/bpb.b16-00638
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Treatment with Branched-Chain Amino Acids, Citric Acid, L-Carnitine, Coenzyme Q10, Zinc, and Various Vitamins in Tumor-Bearing Mice

Abstract: A functional dietary supplement (FDS) containing Coenzyme Q10, branched-chain amino acids and L-carnitine was administered to tumor-bearing mice, investigating its effects on tumor and muscle tissues. Experiment (A): B16 melanoma cells were implanted subcutaneously into the right side of the abdomen of 8-to 9-week-old C57BL/6J mice. The mice were divided into two groups: a FDS group that received oral administration of FDS (n=10), and a control group that received oral administration of glucose (n=10). The mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Furthermore, this combination attenuated weight loss and inflammatory markers, and reduced pathogen levels and bacterial translocation in a chemotherapy model (140). In mice bearing the B16 melanoma, the effect of a multi-nutrient intervention with BCAAs, citric acid, Lcarnitine, coenzyme Q10 and various vitamins and minerals was investigated on the development of cancer cachexia (141). The mice receiving the intervention diet showed a higher cumulative food intake compared to tumor-bearing control.…”
Section: Multinutrient Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this combination attenuated weight loss and inflammatory markers, and reduced pathogen levels and bacterial translocation in a chemotherapy model (140). In mice bearing the B16 melanoma, the effect of a multi-nutrient intervention with BCAAs, citric acid, Lcarnitine, coenzyme Q10 and various vitamins and minerals was investigated on the development of cancer cachexia (141). The mice receiving the intervention diet showed a higher cumulative food intake compared to tumor-bearing control.…”
Section: Multinutrient Interventionsmentioning
confidence: 99%
“…In addition, tumor weight was significantly lower and lung metastasis of the B16 melanoma cells were absent in the intervention group. However, attenuation of muscle tissue loss was only observed for the suprahyoid muscles in the neck but not for gastrocnemius or soleus muscles in the lower leg (141). More recently, the effect of total nutrition formula on LLCbearing mice was investigated (142).…”
Section: Multinutrient Interventionsmentioning
confidence: 99%
“…To the best of our knowledge, the present study is the first to have reported the inhibitory effect of CoQ10 on the migration of cancer cells. It has been previously reported that a functional dietary supplement containing CoQ10 branched-chain amino acids and L-carnitine completely inhibited the metastasis of melanoma to the lung (84). In addition, exogenous CoQ10 reduced matrix metalloproteinases 2 (MMP-2) activity in a breast cancer cell line (MCF-7), suggesting the importance of coenzyme Q10 on cell invasion effector molecules (85).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this combination attenuated weight loss and inflammatory markers, and reduced pathogen levels and bacterial translocation in a chemotherapy model (142). In mice bearing the B16 melanoma, the effect of a multi-nutrient intervention with BCAAs, citric acid, L-carnitine, coenzyme Q10 and various vitamins and minerals was investigated on the development of cancer cachexia (143). The mice receiving the intervention diet showed a higher cumulative food intake compared to tumor-bearing control.…”
Section: Chaptermentioning
confidence: 99%
“…In addition, tumor weight was significantly lower and lung metastasis of the B16 melanoma cells were absent in the intervention group. However, attenuation of muscle tissue loss was only observed for the suprahyoid muscles in the neck but not for gastrocnemius or soleus muscles in the lower leg (143). More recently, the effect of total nutrition formula on LLC-bearing mice was investigated (144).…”
Section: Chaptermentioning
confidence: 99%